Web 2.0 in Computer-Assisted Language Learning: a research synthesis and implications for instructional design and educational practice - Parmaxi, Antigoni; Zaphiris, Panayiotis (My University, 2017)
his study explores the research development pertaining to the use of Web 2.0 technologies in the field of Computer-Assisted Language Learning (CALL). Published research manuscripts related to the use of Web 2.0 tools in CALL have been explored, and the following research foci have been determined: (1) Web 2.0 tools that dominate second/foreign language classroom; (2) learning/Second Language Acquisition theories that guide their use; (3) skills that Web 2.0 technologies support; (4) reported advantages and challenges in harnessing Web 2.0 tools; and (5) task design considerations. Findings of this study delineate how Web 2.0 tools are utilized in CALL and capitalize Web 2.0 features employed for different types of pedagogical activities. This paper argues that social technologies are valuable tools in the language classrooms but entail challenges regarding their theoretical and pedagogical alignment. The study concludes with some discussion and implications for instructional designers and practitioners.
Keywords: Social technologies; Social media; Social networks; Lliterature review; Research synthesis; Pedagogy